2005
DOI: 10.1088/0953-8984/17/39/006
|View full text |Cite
|
Sign up to set email alerts
|

Collective dynamics in crystalline polymorphs of ZnCl2: potential modelling and inelastic neutron scattering study

Abstract: We report a phonon density of states measurement of α-ZnCl 2 using the coherent inelastic neutron scattering technique and a lattice dynamical calculation in four crystalline phases of ZnCl 2 using a transferable interatomic potential. The model calculations agree reasonably well with the available experimental data on the structures, specific heat, Raman frequencies and their pressure variation in various crystalline phases. The calculated results have been able to provide a fair description of the vibrationa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Initially, the simulation was run at a temperature of 6000K to ensure a random distribution of ions. The temperature was then reduced to 3000K, and then to 1000K, where the system was still comfortably above its melting temperature of 593K [17]. To form a glass model, the liquid system was quenched from 1000K to 300K at a rate of 10 13 K/s.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Initially, the simulation was run at a temperature of 6000K to ensure a random distribution of ions. The temperature was then reduced to 3000K, and then to 1000K, where the system was still comfortably above its melting temperature of 593K [17]. To form a glass model, the liquid system was quenched from 1000K to 300K at a rate of 10 13 K/s.…”
Section: Computational Methodologymentioning
confidence: 99%
“…In their Comment, Kalampounias et al have suggested that the sample of α-ZnCl 2 prepared by us [1] may contain H 2 O.…”
mentioning
confidence: 94%
“…Further, the neutron-weighted phonon density of states, as measured [1] for our sample for the range of energy transfer up to 60 meV, does not show any of the known peaks (for example, at around 6 and 25 meV) of the vibrations of water molecules [3].…”
mentioning
confidence: 99%